Culture Shock Experienced by Indonesian Students in U.S. - Hesty Hasyim; Serliah Nur (Institut Agama Islam Negeri Palopo, 2022)
Cultural differences make Indonesian students have the opportunity experienced culture shock. This study aims to find the dimension and the factors that affect of culture shock experienced by Indonesia students in the U.S. This study used a qualitative method with Ward’s theory about the dimension of culture shock and Rajasekar’s categories of factor caused by culture shock. The finding of this research found that there are three dimensions experienced by Indonesian students, namely affective dimension which the students experienced anxiety or frightness while in the host culture, behavior dimension which the students experienced rules or habits error while in the host culture, and cognitive dimension which the students create their social identification because of different culture. There are 11 categories that affect culture shock experienced, those are communication, language, dress, individualism, food, structure, perceptions, religion, time orientation, tradition, and weather.